2004
DOI: 10.1023/b:nere.0000023605.68408.fb
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ketamine Vary Among Inbred Mouse Strains and Mimic Schizophrenia for the P80, but not P20 or N40 Auditory ERP Components

Abstract: N-methyl-D-aspartate (NMDA) antagonists produce behavioral and electrophysiological effects similar to schizophrenia. The mouse P20, N40, and P80 event related potential (ERP) components were analyzed for genetic variance among inbred strains and ketamine-induced differences to model abnormalities in the P50, N100, and P200 in schizophrenia. Ketamine increased P20/N40 amplitude and decreased P80 amplitude. Therefore, the effects of ketamine in mice are inconsistent with alterations in the corresponding P50 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 64 publications
9
87
0
Order By: Relevance
“…The lack of ketamine effect on AEP-based P50 is a replication of previous reports, all of which showed that ketamine itself did not significantly affect P50 gating in humans (van Berckel et al, 1998;Oranje et al, 2002). Animal studies suggest that ketamine has either no effect (de Bruin et al, 1999) or even increase in P20/N40 (the rodent AEP component believed to be equivalent to human P50) (Connolly et al, 2004). The negative findings can be due to a lack of significant NMDA receptor involvement in sensory gating, insufficient dose of ketamine, or methodology issues.…”
Section: Discussionsupporting
confidence: 84%
“…The lack of ketamine effect on AEP-based P50 is a replication of previous reports, all of which showed that ketamine itself did not significantly affect P50 gating in humans (van Berckel et al, 1998;Oranje et al, 2002). Animal studies suggest that ketamine has either no effect (de Bruin et al, 1999) or even increase in P20/N40 (the rodent AEP component believed to be equivalent to human P50) (Connolly et al, 2004). The negative findings can be due to a lack of significant NMDA receptor involvement in sensory gating, insufficient dose of ketamine, or methodology issues.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, we have included analysis of the P20 component in an attempt to further characterize the effects of antipsychotic treatment across a broader array of endophenotypic markers related to schizophrenia. Previous studies of a paired click-gating task in C57Bl/6J mice in our group found a mean amplitude of 26 mV for the P20 evoked potential (Connolly et al, 2004). Power analyses indicate that there is an 89% probability of detecting a meaningful difference of 10 mV (40%) of the expected mean, with a case correlation of 0.1 and a sample size of eight mice per group, as designed in the current report.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, previous studies have shown that the mouse AEP peaks P1, N1, and P2 display refractory curves comparable to their putative human correlates (P1, N1, P2) (Umbricht et al, 2004b;Maxwell et al, 2004). Also, in two mouse studies that investigated the effects of pharmacological NMDAR blockade P1 was increased and N1 changed dependent on mouse strain (Maxwell et al, 2006;Connolly et al, 2004). However, since only one long ISI (9 s) was used in these studies, the effect of NMDAR antagonism on responses to tones with short ISIs in mice is unknown.…”
Section: Aep Peak Refractorinessmentioning
confidence: 72%
“…Early auditory sensory processing deficits in NR1 mutants S Bickel et al mutant mice was caused by reduced suppression of the response to the second tone (Figure 1). Based on previous studies, we reason that the mouse correlates of the P50 and N100 are the P20 and N40 respectively (named P1 and N1 in this paper) (Umbricht et al, 2004b;Connolly et al, 2004;Siegel et al, 2003). Most gating studies in humans have focused on the P50 component of the human auditory AEP and only few on the N100.…”
Section: Auditory Gatingmentioning
confidence: 94%
See 1 more Smart Citation